“AN EMPIRICAL STUDY OF LINKING BETWEEN TALENT AND KNOWLEDGE MANAGEMENT WITH RESPECT TO IT INDUSTRIES IN PUNE, MAHARASHTRA (INDIA).” (IITM Journal of Business Studies, 2024)
This paper aims to explain systematic applied  study of Talent Management (TM) and  Knowledge Management (KM) assembly in  an Information Technology (IT) industry  in Pune, Maharashtra (India). Scope of  research study compacts IT organizations  in Pune, Maharashtra (India). This article  kindles talent management and knowledge  management connecting variables and its  effectiveness in performance of 93 IT based  firms situated at Pune. The employees who  are working in organizations and creates their  own creations with own talents are called as  “Knowledge workers” also termed as “Talents”  for an organization. These creation is shared,  transformed , captured in organizational  process for organizational strategies termed  as “Knowledge” Catherine L Wang et.al  (2003).The objectives of this research study  is to study the concept of talent management  and knowledge management and examines  different aspects of its connecting variables and  its performance efficiency in IT organizations.  Findings of the study will help IT organizations  to improve their Talent Management and  Knowledge Management connecting process  and factors to enhancing overall performance  and effectiveness. Researcher provide  Talent Management (TM) and Knowledge  Management (KM) linking model on the basis  of empirical analytical study.
Keywords: Talent; Talent Management(TM); Knowledge; Knowledge Management (KM); Information Technology (IT) firms